Analyzing Stock Markets using Data Warehousing - Mujtaba, S. M.; Nadeem, Mohammed (JISR management and social sciences & economics, 2006)
Today, almost all the stock markets disseminate data in real time. Real time data is of great importance to day traders who keep track of each and every price movement. However, daily trading data is always important for all investor classes and most importantly, to the technical analysts (people who analyze and predict stocks based on historical data). This paper covers areas of interest in statistics, financial technical analysis and data warehousing. This research work firstly identifies a data warehouse design model which is best suited for stock market technical analysis and secondly provides a framework for technical analysts based on standard tools available in the industry.